Modification Method and Performance Analysis of Automobile Steering Rocker Shaft Non-circular Gear Sector - Ding Guolong; Yu Jinfang; Ming Tingbo; Zhang Yali (Jixie chuandong)
The transmission performance of the recirculating ball steering is closely related to the tooth profile shape of the rocker shaft non-circular gear sector. Aiming at the problem of the mesh clearance required by different angles is different between steering gear and rack,a means is proposed to repair the rocker arm shaft by using the varying-modification-coefficient modification method. The varying-modification-coefficient modification method is compared with eccentric modification method and the meshing motion of two kinds of gear rack pairs is analyzed,the related parameters of the gear sector is calculated,and two kinds of NC machining methods are given. The processing simulation is carried out in MATLAB,and the tooth profile coordinates of the two types of modification methods are obtained. Taking into account the actual assembly for the fixed axis transmission,two kinds of rack and pinion gear transmission clearance are calculated. Finally,the driving force which is analyzed by using ADAMS shows that,the two kinds of modification methods can effectively reduce the transmission of meshing force.